POLA PENGGUNAAN BAHASA DALAM INTERAKSI PEMBELAJARAN BAHASA INDONESIA UNTUK MAHASISWA ASING (BIPA) - Indrariani, Eva Ardiana (Lingua Scientia, 2016)
Indonesian studies for foreign speakers is still a new feld. Verbal behavior between lecturers and foreign students in this study approached with sosiopragmatik theory. The data collection is done by: participatory observation; structured interviews; and in-depth interviews. In the data collection tools used in audio recorder, a camera, and stationery. Analyzed using qualitative analysis with the methods of analysis: descriptive and categorical, then, theoretically interpret this categorization. In this study found six languages, beside Indonesian langiage used in learning interactions: English, French, Arabic, Chinese, Myanmar, and Java. English is used to help better understand Indonesian foreign students (disclosure purposes). French is used for setting the example. Arabic and Myanmar used to frequently asked questions concept. Chinese used to explain one of the vibrant Chinese culture in Indonesia. Java language is used to explain the meaning of the word / name from the Javanese and to express emotions. In quantitative terms, the use of the English language is more prominent than the use of another language. It is mainly found in the verbal behavior Lecturer and Lecturer Two Three.